2,7-disubstituted amidofluorenone derivatives as inhibitors of human telomerase - Perry, PJ; Read, MA; Davies, RT; Gowan, SM; Reszka, AP; Wood, AA; Kelland, LR; Neidle, S (Journal of medicinal chemistry, 1999)
Telomerase is a major new target for the rational design of novel anticancer agents. We have previously identified anthraquinone-based molecules capable of inhibiting telomerase by stabilizing G-quadruplex structures formed by the folding of telomeric DNA. In the present study we describe the synthesis and biological evaluation of a series of analogous fluorenone-based compounds with the specific aims of, first, determining if the anthraquinone chromophore is a prerequisite for activity and, second, whether the conventional cytotoxicity inherent to anthraquinone-based molecules may be reduced by rational design. This fluorenone series of compounds exhibits a broad range of telomerase inhibitory activity, with the most potent inhibitors displaying levels of activity (8-12 mu M) comparable with other classes of G-quadruplex-interactive agents. Comparisons with analogous anthraquinone-based compounds reveal a general reduction in the level of cellular cytotoxicity. Molecular modeling techniques have been used to compare the interaction of fluorenone- and analogous anthraquinone-based inhibitors with a human G-quadruplex structure and to rationalize their observed biological activities.